Perekonomian Indonesia Pasca Pemutusan Kontrak dengan IMF - Edy Suandi Hamid (Universitas Islam Indonesia, 2003)
IMF Contract exit constitutes the best choice particularly in escaping the dependence of Indonesia from foreign intervention regarding economy policies. Thefund andnatural resources of Indonesia could be expected to pay Indonesia loan from IMF nowadays. In this sense, emotional attitude and narrow nationalism are not enough to avoid the negative Influence of IMF exit strategy. So, an anticipative step and radical policy should beconducted by Indonesian government tostopcorruption, collusion, and nepo tism practices strictly and consequently. Besides, ending IMF contract in Indonesia could be used for both modern sector and traditional sector. Traditional sector, it is clear that marginalized. The traditional sector indicates survival sector and cancreate a vocation.